Building the motivations towards E-Shopping Scale among Umm Al-Qura University students - Al-Omayri, Tahani Qablan (Journal of Educational and Psychological Sciences, 2023)
The current study aimed to construct a measure of motivation towards electronic shopping among Umm Al-Qura University students, and relied on the descriptive approach, and the scale in its initial form consisted of (49) items..It was applied to a stratified random sample of (1055) Umm Al-Qura University students in the year 1443 AH, where it was presented to (10) of the arbitrators, which resulted in the deletion and modification of some paragraphs, and thus the scale became in its initial form (46) paragraphs, and the validity of it was confirmed. And the stability of the initial image on an exploratory sample of (100) Umm Al-Qura University students, and the exploratory factor analysis was used to reveal the factorial structure of the items. (13) Items for the psychological motives dimension, (9) items for the social motives dimension, and (13) items for the practice and performance motives dimension. To ascertain the psychometric properties of the scale, the final image was applied to a stratified random sample of (1055) Umm Al-Qura University students. Cronbach’s alpha method and recommends the application of the scale as a scientific tool to measure the motives towards e-shopping among university students by companies and investors, as it has been proven that the scale has acceptable psychometric properties in terms of validity and reliability.